Creole seed fair parties: building resistance practices in front of conventional agriculture (Desenvolvimento em Questão, 2024)
The Creole Seed Fair Festivals have multiplied in the State of Paraná, they are spaces for exchanging knowledge, political articulation and actions aimed at the preservation, multiplication and production of Creole seeds and the strengthening of agroecology and agrobiodiversity. Between the years 2020 and 2024, in Paraná, eleven Crioula Seed Fair Festivals were observed, which were not only configured as festivals or cultural events, but also as an arena for territorial praxis and dynamic spaces of intense political, discursive and contestatory movements against the conventional agriculture model. The objective of the investigation is to understand how Creole seed fairs constitute spaces of resistance and transformation, highlighting the centrality of Creole seeds and agroecology. The research used Participant Observation and Oral History, focusing on the subjects' views on the importance of fairs and their world views, based on their narratives and lived experience. The Creole seeds saved, passed on, exchanged and cultivated aim to strengthen agroecology in a re-territorializing movement for the seed within the spaces of the Creole Seed Fair Festivals. At the same time, they transcend them, they are resistance to an agricultural model that uses transgenic seeds and that disregards diversities, heterogeneities and pluridiversities. The lived space is in everyday life and collective construction, it is in this action that resistance lies. The Creole Seed Fair Festivals held within traditional communities have a different relevance. Those carried out outside these territories focus on dialogue, sharing, commercialization and exchange of seeds.
Keywords: criollo seed fair; pluriverso; participant observation research